Xenoglosofilia: Gambaran Self-Esteem pada Generasi Z yang Gemar Mencampur Bahasa - Sundani, Muhammad Fayyadh Fathur Rizky; Mohammad Rifki Aji Budiman; Salamatul Mardliyyah; Neng Wulan Sari; Syifa Putri Salsabila (Psikodinamika: Jurnal Literasi Psikologi, 2024)
The influence of globalization has caused the emergence of xenoglossophilia, which is the tendency to mix languages. One of the factors driving this phenomenon is the assumption that foreign languages are superior, so mixing languages is considered cool. This study was conducted to determine the description of self-esteem in the Z Generation who likes to mix languages (xenoglossophilia). The study used quantitative methods by using the Rosenberg Self-Esteem Scale (RSES) measuring instrument and descriptive data analysis techniques. Data collection using a questionnaire with 120 respondents of students. This study shows that self-esteem in the majority of Generation Z, especially Universitas Pendidikan Indonesia students with xenoglosophilia, is in the high category. From the results of this study, it can show that self-esteem in most of Generation Z, especially students of Universitas Pendidikan Indonesia. Who have xenoglossophilia conditions are in the high category with two important aspects, namely aspects of high self-acceptance and aspects of self-respect that tend to be low. This shows that there is indeed a representation on these two variables.